Adaptation and validation of the Organizational Description Questionnaire (Bass & Avolio, 1992). A study with civilian and military population. - Nader, Martín (2006)
Present data are gathered from a sample of civil population (n = 1003) and military cadets (n =488). The main objective of this study was to obtain the psychometric properties (reliability and validity) of the Organizational Description Questionnaire (Bass & Avolio, 1992). In reference to reliability, results show good levels of internal consistency for both dimensions, although they are a little bit lower for the transactional culture dimension for both populations. In reference to validity, the evidence allows affirming that the test is valid. The factorial analysis showed that the items group in 2 factors that respond to the theoretical proposal made by the authors of the test. Lastly, we have found differences between leaders and followers on the perception of organizatio-nal culture for both populations.